2008
DOI: 10.1007/s10729-007-9050-7
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and associated respiratory morbidity in Delhi

Abstract: As a rapidly expanding centre of government, trade, commerce and industry, Delhi, the Indian capital, presents an instructive location for studying the possible association between air pollution and adverse health effects. This study tries to determine the association, if any, between the air pollutants--sulphur dioxide, nitrogen dioxide, carbon monoxide, ozone, suspended particulate matter and respiratory suspended particulate matter--and daily variations in respiratory morbidity in Delhi during the years 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…All six found positive associations with SO 2 (two nonsignificant) that ranged from 0.13% to 8.2% compared with -0.5-22.5% for the previous estimates. Where there was adjustment for other pollutants (Cakmak, Dales & Judek, 2006b;Jayaraman & Nidhi, 2008;Leem et al, 1998), the estimates were reduced and remained significant in only one study (Cakmak, Dales & Judek, 2006b). …”
Section: Short-term Exposure and Respiratory Hospital Admissionsmentioning
confidence: 99%
See 3 more Smart Citations
“…All six found positive associations with SO 2 (two nonsignificant) that ranged from 0.13% to 8.2% compared with -0.5-22.5% for the previous estimates. Where there was adjustment for other pollutants (Cakmak, Dales & Judek, 2006b;Jayaraman & Nidhi, 2008;Leem et al, 1998), the estimates were reduced and remained significant in only one study (Cakmak, Dales & Judek, 2006b). …”
Section: Short-term Exposure and Respiratory Hospital Admissionsmentioning
confidence: 99%
“…Papers published since (or not considered in) the EPA's 2008 review also reported positive (though not always statistically significant) single-pollutant associations for hospital admissions and emergency room visits for: (a) asthma (Bell, Levy & Lin (2008), Colais et al, 2009;Giovannini et al, 2010;Halonen et al, 2008;Jalaludin et al, 2008;Samoli et al, 2011a;Szyszkowicz, 2008;Ueda, Nitta & Odajima, 2010;Villeneuve et al, 2007) and (b) respiratory causes (Colais et al, 2009;Eilstein et al, 2004;Faustini et al, 2013;Granados-Canal et al, 2005;Giovannini et al, 2010;Jayaraman & Nidhi, 2008;Thach et al, 2010;Vigotti et al, 2010).…”
Section: Mortalitymentioning
confidence: 99%
See 2 more Smart Citations
“…51 Jayaraman et al in Delhi showed that a 10-microgram rise in O 3 led to increase in respiratory morbidity (RR = 1.03). 52 …”
Section: Health Effects Of Ozone: Indian Literaturementioning
confidence: 99%